Narrow versus broad judicial decisions. (July 2014) - Fox, Justin; Vanberg, Georg
A central debate among judges and legal scholars concerns the appropriate scope of judicial opinions: should decisions be narrow, and stick to the facts at hand, or should they be broad, and provide guidance in related contexts? A central argument for judicial 'minimalism' holds that judges should rule narrowly because they lack the knowledge required to make general rules to govern unknown future circumstances. In this paper, we challenge this argument. Our argument focuses on the fact that, by shaping the legal landscape, judicial decisions affect the policies that are adopted, and that may therefore subsequently be challenged before the court. Using a simple model, we demonstrate that in such a dynamic setting, in which current decisions shape future cases, judges with limited knowledge confront incentives to rule broadly precisely because they are ignorant.